Interventional closure of artificial vascular anastomotic fistula after aortic replacement: a case report - Qingwang Hou; Tongfeng Chen; Xiaohu Wang; Yipin Zhao; Chong Chen; Yuhao Liu (Frontiers in Cardiovascular Medicine, 2025)
Two years ago, the patient suffered from type A aortic dissection. As a result, partial aortic dissection artificial vascular replacement and partial aortic arch artificial vascular replacement were performed. Six months after the operation, an anastomotic fistula in the ascending aorta was detected, which subsequently progressed to chronic heart failure of New York Heart Association (NYHA grade) class III. After eliminating the operation - related contraindications, the patient successfully had the fistula occluded through transcatheter ascending aorta - right atrial fistula in our hospital. After the operation, no abnormal shunt was found, and the short - term treatment effect was satisfactory.